Perilla frutescens as potential antimicrobial modifier to against forage oat silage spoilage - Li, Xiaomei; Chen, Fei; Xiong, Yi; Guo, Linna; Xu, Jingjing; Lin, Yanli; Ni, Kuikui; Yang, Fuyu (Frontiers in Microbiology, 2022)
The aim of this study was to investigate the influence of Perilla frutescens, alone or in combination with Lactobacillus plantarum a214 or citric acid, on forage oat silage quality, bacterial and fungal microbiological profile during ensiling and aerobic exposure. With the exception of Perilla frutescens, all additives could improve silage quality of forage oat based on lower ammonia-nitrogen content and higher residual of water-soluble carbohydrates during anaerobic fermentation compared to control silage, especially in Perilla frutescens combined with citric acid (CAPF). Lactobacillus was the dominant bacteria in all silages, while CAPF group increased the relative abundance of Lactobacillus lindneri and Lactobacillus brevis compared to control silage. The application of Perilla frutescens suppressed the relative abundance of yeasts such as Pichia fermentans and Wickerhamomyces anomalus in response to aerobic exposure, especially in CAPF treatment, leading to high acetic acids and lower dry matter loss, as well as good aerobic stability. Therefore, Perilla frutescens, alone or in combination with citric acid, has potential to improve aerobic stability of forage oat silage by shifting bacterial and fungal community composition, and can be used as new additive to prepare high-quality silage for animal production.